2016
DOI: 10.1007/s11606-016-3758-3
|View full text |Cite
|
Sign up to set email alerts
|

Describing Failure in a Clinical Clerkship: Implications for Identification, Assessment and Remediation for Struggling Learners

Abstract: BACKGROUND: In addition to training future members of the profession, medical schools perform the critical role of identifying students who are failing to meet minimum standards in core competencies. OBJECTIVE: To better understand reasons for failure in an internal medicine clerkship. DESIGN: A qualitative content analysis of letters describing reasons for students' failure. PARTICIPANTS: Forty-three students (31 men) who failed the internal medicine clerkship at the University of Minnesota Medical School, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Many of the students perceived problems in more than one domain. Similar findings were also noted in another study [35]. Previous studies have also shown that underperformers lack the necessary study skills to perform well in examinations.…”
Section: Discussionsupporting
confidence: 89%
“…Many of the students perceived problems in more than one domain. Similar findings were also noted in another study [35]. Previous studies have also shown that underperformers lack the necessary study skills to perform well in examinations.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to insufficient knowledge, students in clerkships can struggle with patient presentation skills, foundational communication skills (e.g. introducing oneself), physical examination skills, and the application and synthesis of knowledge to create individualized patient plans [8, 9]. For residents and foundation years (the 2 years immediately after medical school in the UK), knowledge can continue to be a major area of struggle [5, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, the critical deficiency Binefficiency^was present in 8 (19%) of our 43 students who failed the medicine clerkship. 1 The lower frequency of this critical deficiency in our sample as compared to the frequency of difficulties with efficiency/organization noted by residency program directors 2 may reflect, as they suggest, that efficiency is not yet expected from medical students. It is also possible that behaviors one might interpret as inefficient are actually represented in other domains and coded in our study as deficiencies such as Blate,^Bfailure to complete course work,^or even perhaps Bdisinterested^or Binadequate documentation.^Perhaps one could even attribute NBME Subject Exam failure to inefficient or disorganized study habits.…”
mentioning
confidence: 58%